2018
DOI: 10.1111/ases.12646
|View full text |Cite
|
Sign up to set email alerts
|

Transanal completion proctectomy with close rectal dissection and ileal pouch‐anal anastomosis for ulcerative colitis

Abstract: Our initial experience with transanal completion proctectomy and ileal pouch-anal anastomosis shows promising results, demonstrating the feasibility of the transanal approach in patients with UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Table 1, [10][11][12][13][14][15][16][17] [24][25][26][27][28][29] highlight the main characteristics of the studies identified in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1, [10][11][12][13][14][15][16][17] [24][25][26][27][28][29] highlight the main characteristics of the studies identified in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The technique was first described in human by the Barcelona team in 2015 after the initial animal and cadaveric experiences, with a first case series involving 16 cases 8 . Since then, we found in literature 5 single-case reports ,,,, , 4 further case series ranging from 8 to 18 cases 9,10,11,12 and three multicentric experiences, reporting partially overlapping cohorts of 97 13 , 62 and 100 14 cases. Described cases vary in indication from IBD to FAP.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited evidence, other authors advocate against being dogmatic in the application of the transanal approach to all patients, specifically thin and female patients, as it is argued that there is no perceived advantage over a pouch created laparoscopically. 20 However, there is evolving evidence that the transanal approach may have some benefit in several postoperative outcomes. Short-term morbidity rates of Ta-IPAA were reported to be 33% compared with 41% in traditional abdominal IPAA in a retrospective cohort study, but these findings were not statistically significant.…”
Section: Potential Advantages Of Ta-ipaamentioning
confidence: 99%